KAJIAN MINAT MASYARAKAT TERHADAP PARIWISATA ALTERNATIF DAN WISATA PEDESAAN MELALUI GOOGLE TRENDS - Zahrotun Satriawati; Hendi Prasetyo; Novi Irawati (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2023)
The development of tourism during the Covid-19 pandemic experienced a transition towards alternative tourism. Public interest in rural-based alternative tourism is a choice of travel in the search aspect through the Google search engine. This can be known from search results by analyzing Google Trends. Google Trends is a tool that can be used to collect and analyze information about web-based information search behavior. The purpose of this study is to examine the development trend of searching for types of tourism related to alternative tourism and rural tourism in Indonesia using Google Trends Analysis. The search method using Google Trends was carried out on data for a period of 2 years from 2020 to 2022 with the keywords